Production and analysis of synthesized bacterial cellulose by Enterococcus faecalis strain AEF using Phoenix dactylifera and Musa acuminata fruit extracts - AL-Hasabe, Ashraf Sami Hassan; Abdull Razis, Ahmad Faizal; Baharum, Nadiya Akmal; Yu, Choo Yee (Springer Science and Business Media, 2024)
Bacterial cellulose (BC) is a highly versatile biopolymer renowned for its exceptional mechanical strength, water retention, and biocompatibility. These properties make it a valuable material for various industrial and biomedical applications. In this study, Enterococcus faecalis synthesized extracellular BC, utilizing Phoenix dactylifera and Musa acuminata fruit extracts as sustainable carbon sources. LC-MS analysis identified glucose as the primary carbohydrate in these extracts, providing a suitable substrate for BC production. Scanning Electron Microscopy (SEM) revealed a network of BC nanofibers on Congo red agar plates. ATR-FTIR spectroscopy confirmed the presence of characteristic cellulose functional groups, further supporting BC synthesis. X-ray diffraction (XRD) analysis indicated a high crystallinity index of 71%, consistent with the cellulose I structure, as evidenced by peaks at 16.22°, 21.46°, 22.52°, and 34.70°. Whole-genome sequencing of E. faecalis identified vital genes involved in BC biosynthesis, including bcsA, bcsB, diguanylate cyclase (DGC), and 6-phosphofructokinase (pfkA). Antibiotic susceptibility tests revealed resistance to cefotaxime, ceftazidime, and ceftriaxone, while susceptibility to imipenem was observed. Quantitative assessment demonstrated that higher concentrations of fruit extracts (5.0–20 mg/mL) significantly enhanced BC production. Cytotoxicity testing via the MTT assay confirmed excellent biocompatibility with NIH/3T3 fibroblast cells, showing high cell viability (97–105%). Unlike commonly studied Gram-negative bacteria like Acetobacter xylinum for BC production, this research focuses on Gram-positive Enterococcus faecalis and utilizes Phoenix dactylifera and Musa acuminata fruit extracts as carbon sources. This approach offers a sustainable and promising avenue for BC production.